Interdiscursive variations: the literature – theory relation - Ѓорѓиева Димова, Марија (Poznańskie Studia Slawistyczne, 2012)
The subject of this paper is the theoretical fiction genre as a manifestation of interdiscursive relations between fiction and theory/criticism. Firstly, this paper offers a brief overview of the  constitutive features  of  the  theoretical  fiction  genre;  and  secondly,  these  features  are interpretatively confirmed through the novel  Papokot na svetot (Navel of the World) by the Macedonian writer, Venko Andonovski.